Doğu Türkçesi Kur’an tefsiri (sâffât, sad ve zümer sûreleri) (inceleme-tenkitli metin-dizġi-tıpkıbasım) - Üngör, Yurdagül Aydın (My University, 2015)
Bu çalışma, Topkapı Sarayı Müzesi Kütüphanesi, III. Ahmet Bölümü, 16 numarada kayıtlı bulunan nüshanın 2. Cildine ait 150a/ 173a varakları üzerinde yapılmıştır. Bu varaklar Saffat, Sad ve Zümer surelerini içermektedir. İstinsah tarihi H. 950/ M. 1543 olan eserin her bir sayfası 27 satırdır. Tezde, İnceleme, Tenkitli Metin, Dizin ve Tıpkıbasım olmak üzere dört bölüm bulunmaktadır. İnceleme bölümünde, Kur’an tefsirleri ile ilgili ncelediğimiz eser ile ilgili bilgiler yer almaktadır. Ayrıca eserin dil özellikleri de bu bölümde verilmiştir. Tenkitli Metin bölümünde Topkapı nüshası ve Yusuf Ağa nüshasını tenkitli metin olarak çeviri yazıya aktarılmıştır. Dizin bölümünde, transkripsiyonu yapılmış metinde yer alan kelimelerin hangi dile ait oldukları ve metindeki anlamları verilmiştir. Tıpkıbasım bölümünde üzerinde çalıştığımız Topkapı nüshası (150a/ 173a) ve Yusuf Ağa nüshasının (489a/ 513a) tıpkıbasımı verilmiştir. Kur’an tercüme ve tefsirleri söz dizimi ve sözlükçülük açısından önemli eserlerdir. Çalıştığımız metin de tefsirli tercüme özelliği taşıdığından Türk dili için öemli bir eserdir. Kur’an, Tefsir, Doğu Türkçesi, Sâffât Suresi, Sad Suresi, Zümer Suresi

It is known that “Tafsir of Quran in Eastern Turkish” which is registered to Topkapı Palace Museum, Library of Ahmed III, number 16 is a manuscript from Shaybanids period. The time of facsimile is determined as 950 (AH)/ 1543 (AD). Each leaf of the manuscript has 27 lines. The study of “Tafsir of Quran in Eastern Turkish” on Saffat, Sad and Zümer Surats have four sections: Analysis, commentary text, index and facsimile. In the section of “Analysis”, there are the characterization of “Tafsir of Quran in Eastern Turkish”, the copyist of the manuscript, its date and place of writing and the physical features of the manuscript. In addition to those characteristics of the manuscript, its phonetic and morphologic features are analyzed too. In the section of “Commentary Text”, there is a comparison between the transcriptions of two copies of the manuscript, Topkapı copy and Yusuf Ağa copy. In “Index” section, there are the words and their meanings with the information of the languages which the words belong to. The words which changed phonetically are also stated with comparison. In “Facsimile” section, there is the facsimile (150a-173a) of the Topkapı copy and the Yusuf Ağa copy of the manuscript which we studied on in this thesis. Translations of Quran and tafsirs of Quran have an important role in lexicography and syntax. The manuscript which we studied on has partly the characteristics of a literally translation and partly the characteristics of the translation with some parables and stories. Hence, it’s a very valuable work for both syntax and the Turkish language. Quran, Tafsir, Eastern Turkish, Saffat, Sad, Zümer, Surat
Keywords: Doğu Türkçesi; Kur’an; Kur’an-ı Kerim; Sad Suresi; Sâffât Suresi; Tarih; Tefsir; Türk Dili; Zümer Suresi